Sickle Cell Disease and Superstitions: An Interesting Study Report - D.P, Swarnali (Indian Journal of Pharmacy Practice)
This study focuses on four interesting cases of sickle cell anaemia in rural areas of Chhattisgarh (CG) state. CG is a young state of growing central India with highest resources of minerals, iron, herbals and rice cereals. These patients were identified during a sickle cell disease management programme conducted by Faculty of Pharmaceutical sciences, Shri Shankaracharya Group of Institutions, Bhilai, CG. The study reveals all the patients were from poor backward communities. Symptoms related to malnutrition and infections were mostly intermingled with anaemia but all of them were least interested to follow any treatment. They were following some 'jaributi' from years which had worsened their conditions. There details history was taken from them and counselled them so that they understand the scope of the problem and participate in the management of the disease.
Keywords: Blood disorder; Chhattisgarh; India; Sickle cell anaemia; patient counselling